HABITUS SENIMAN WAYANG TOPENG MALANG DI PADEPOKAN ASMORO BANGUN - Amelia, Avita (Paradigma, 2021)
ABSTRACT This study addresses associated with habitus artists Wayang Topeng Malang in padepokan Asmoro Bangun. A group of artists that have a culture Pendalungan as the mix of cultures between the ethnicities of Java to Madura. A group of artists Pendalungan that has a blood descendant of mbah Karimun of course there are still thick with the values of the maestro Mask Malang. On the other hand, a group of artists Pendalungan other has a habit of its own in art, because of the different understanding. Therefore, the purpose of this research is to identify the culture Pendalungan in Wayang Topeng Malang Asmoro Bangun and habitus of the actors of his art, which is analyzed through the theory of Habitus Pierre Bordieu. The method used in this research is qualitative approach with ethnographic James P. Spraedly. Location of the research 2 conducted at padepokan Asmoro Bangun. The subject comes from a group of artists Wayang Topeng Malang Asmoro Bangun is still active. The results of this study show that the artist Wayang Topeng Malang who have breeds breeds of mbah Karimun has habitus berspiritual and actualization, so that can improve the social status in the society. Different is the case with artist Wayang Topeng Malang in padepokan Asmoro Bangun other. This is due to the owned capital is quite limited, so it must work harder to maintain its existence, even though they have a habitus different. Keywords : Habitus, Artist, Wayang Topeng Malang, Pendalungan Society